Kadar Mineral Kalsium Dan Besi Pada Sapi Bali Yang Dipelihara Di Lahan Persawahan (LEVEL OF MINERAL CALCIUM AND IRON ON THE BALI CATTLE BEING FARMEDIN THE RICE FIELD) - Pujiastari, Ni Nyoman Tri; Suastika, Putu; Suwiti, Ni Ketut (Buletin Veteriner Udayana, 2015)
This research aims were to know the levels of calcium and iron mineral in blood serum of balicattle rared on the rise fields. The sample used in this study were blood serums which were takenfrom 15 bali cattles  in District of Tabanan, Bali Province.  Serum samples were analysed by wetdestruction method, used H2SO4 and HNO3 and mineral concentration are read by AtomicAbsorpsion  Spectrofotometry (AAS). The result show that the level of bali cattle calcium mean of6,23±0,019 mg/l and iron  mean 8,387±0,002 mg/l. The conclusion of this research is the level ofcalcium was lower and iron level was higher, campared to the other cattle in the world.
Keywords: bali cattle; minerals; calcium; iron; rice fields